2022
DOI: 10.1007/s12035-022-03054-4
|View full text |Cite
|
Sign up to set email alerts
|

Can the Imbalance between Neurotrophic and Apoptotic Proteins Be the “Beware the Ides of March” for Unaffected Relatives of Schizophrenia Patients?

Abstract: Schizophrenia (SZ) is a mental disorder with a strong genetic basis as well as epigenetic aspects. Siblings of patients with SZ can share certain endophenotypes with the patients, suggesting that the siblings may be important for distinguishing between trait and state markers. In the current study, we aimed to characterize the balance between pro-BDNF/mature BDNF and its receptors p75NTR/TrkB, which is tpa-BDNF pathways proteins and thought to play a role in synaptic pruning as a possible endophenotype of schi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Increased plasma levels of p75 receptor protein are reported in first-episode psychosis patients compared to clinical high-risk individuals and controls ( He et al, 2019 ), with higher ratios of p75/TrkB protein found in serum of first-episode psychosis patients compared to unaffected siblings and controls ( Yesilkaya et al, 2022 ), reflecting a trophic imbalance preceding diagnosis and treatment that may favour apoptotic functions of the receptor. Whilst plasma p75 protein levels were found to positively correlate with positive and negative symptom scores in schizophrenia ( Zakowicz et al, 2023 ), other studies report no changes in p75 protein in the plasma of schizophrenia patients compared to controls ( Haack et al, 1999 ; Yesilkaya et al, 2022 ), with some reporting lower serum levels of p75 receptor protein ( Zakharyan et al, 2014 ; Chen et al, 2017 ; Turhan et al, 2016 ). A potential contributor to the heterogeneous results of studies assessing peripheral p75 receptor expression in schizophrenia is the prevalence of single nucleotide polymorphisms (SNPs) of the p75 receptor evident in patients.…”
Section: Alterations In P75 Receptor Expression In Schizophreniamentioning
confidence: 99%
“…Increased plasma levels of p75 receptor protein are reported in first-episode psychosis patients compared to clinical high-risk individuals and controls ( He et al, 2019 ), with higher ratios of p75/TrkB protein found in serum of first-episode psychosis patients compared to unaffected siblings and controls ( Yesilkaya et al, 2022 ), reflecting a trophic imbalance preceding diagnosis and treatment that may favour apoptotic functions of the receptor. Whilst plasma p75 protein levels were found to positively correlate with positive and negative symptom scores in schizophrenia ( Zakowicz et al, 2023 ), other studies report no changes in p75 protein in the plasma of schizophrenia patients compared to controls ( Haack et al, 1999 ; Yesilkaya et al, 2022 ), with some reporting lower serum levels of p75 receptor protein ( Zakharyan et al, 2014 ; Chen et al, 2017 ; Turhan et al, 2016 ). A potential contributor to the heterogeneous results of studies assessing peripheral p75 receptor expression in schizophrenia is the prevalence of single nucleotide polymorphisms (SNPs) of the p75 receptor evident in patients.…”
Section: Alterations In P75 Receptor Expression In Schizophreniamentioning
confidence: 99%